2018
DOI: 10.1002/gps.4932
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sociodemographic and physical activity on cognitive function in older adults: A nationwide cross‐sectional survey

Abstract: OAs' sex, age, co-residence, years of schooling, and IADL were significantly associated with cognitive function. Improving OAs' IADL, especially in lower social classes, may help to improve the overall cognitive function of the OAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
14
1
Order By: Relevance
“…Higher prevalence of dementia was found among the younger elderly, aged 65-69 years, in Latin American countries compared with developed nations, whereas the older elderly presented a higher rate of dementia in developed countries (3) . These findings corroborate those of studies associating differences in functional or cognitive performance with social, ethnic, economic, cultural or demographic diversity (4,5,6,7) , as well as with genetic factors (8) . Cognitive-behavioral and functional-structural changes may occur as a result of education, a multidimensional variable that encompasses quality of life, socioeconomic level, and activities of daily living (9) .…”
Section: Introductionsupporting
confidence: 88%
“…Higher prevalence of dementia was found among the younger elderly, aged 65-69 years, in Latin American countries compared with developed nations, whereas the older elderly presented a higher rate of dementia in developed countries (3) . These findings corroborate those of studies associating differences in functional or cognitive performance with social, ethnic, economic, cultural or demographic diversity (4,5,6,7) , as well as with genetic factors (8) . Cognitive-behavioral and functional-structural changes may occur as a result of education, a multidimensional variable that encompasses quality of life, socioeconomic level, and activities of daily living (9) .…”
Section: Introductionsupporting
confidence: 88%
“…Physical functioning, such as ADLs, is a good measurement of functional capacity and a proxy of health status widely used in healthy aging studies (Kojima, 2018;Zeng et al, 2017;Zhang et al, 2019). Previous studies reported that ADL limitations indicated an increased risk of being in the declining group (Hartley et al, 2017;Lindbergh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…8 Each item of the mMMSE was scored as "1" if the answers of participants were correct and "0" if wrong. 8 More correct answers demonstrated better cognitive function. Previous studies 19 have indicated that the reliability of the mMMSE was high (Cronbach's α = 0.98).…”
Section: Cognitive Functioningmentioning
confidence: 99%